IMPLEMENTASI KNOWLEDGE MANAGEMENT SYSTEM PADA UMKM DI KOTA SALATIGA (STUDI KASUS PAK KUN FROZEN FOOD DUSUN NGEPOS) - Abu Rochmad Maulana Shaivudi,; Reza Widhar Pahlevi, (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
Management science is basic knowledge that must be possessed by every business actor in running a business. In order for the application of the management science system in a business to run optimally, business actors must understand and apply management functions including; planning, organizing, staffing, leading, and controlling. This study aims to determine the Implementation of Knowledge Management System in MSMEs in Salatiga City (Case Study of Pak Kun Frozen food). Data from this study was obtained from two resource persons who are owners and employees of Pak Kun Frozen food. This research is qualitative by using direct interview methods at the research location. Data analysis uses methods of data reduction, data display, conclusion drawing and triangulation. The results showed that MSMEs Pak Kun Frozen food has implemented the Knowledge Management System, but there are obstacles related to the lack of employee awareness about management science. Therefore, full support from management and business owners is needed in facilitating employee training and development.